2001
DOI: 10.1046/j.1526-4637.2001.01052.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal Hydromorphone for Chronic Nonmalignant Pain: A Retrospective Study

Abstract: Hydromorphone can be a safe, analgesic alternative for long-term intrathecal management of nonmalignant pain among patients in whom morphine fails because of pharmacological side effects or inadequate pain relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 61 publications
1
43
0
3
Order By: Relevance
“…Among these, 52 articles were excluded from both the effectiveness and complications review based on the same criterion: 26 because they were case reports ; 13 because they did not report data separately for patients with programmable IDDS, 39-51 9 because >10% of the sample had spasticity or a specific disease [52][53][54][55][56][57][58][59][60] ; and 4 because they focused only on patients who had not responded to their first IDDS drug. [61][62][63][64] (Where there was more than 1 reason for exclusion, we noted only the first reason identified.) Twenty other articles were excluded from the effectiveness review; 14 because they did not meet the study methodology criteria 65-78 and 6 because they did not report pre-IDDS data on pain or functioning.…”
Section: Search Resultsmentioning
confidence: 99%
“…Among these, 52 articles were excluded from both the effectiveness and complications review based on the same criterion: 26 because they were case reports ; 13 because they did not report data separately for patients with programmable IDDS, 39-51 9 because >10% of the sample had spasticity or a specific disease [52][53][54][55][56][57][58][59][60] ; and 4 because they focused only on patients who had not responded to their first IDDS drug. [61][62][63][64] (Where there was more than 1 reason for exclusion, we noted only the first reason identified.) Twenty other articles were excluded from the effectiveness review; 14 because they did not meet the study methodology criteria 65-78 and 6 because they did not report pre-IDDS data on pain or functioning.…”
Section: Search Resultsmentioning
confidence: 99%
“…Anderson et al reported 25% improvement in pain control in a group of cancer patients who had inadequate analgesia from morphine. They also reported a significant reduction in side effects such as nausea, vomiting, pruritus and sedation with hydromorphone vs. morphine [59]. Peripheral edema has been reported, similar to morpine [61].…”
Section: Commonly Used Agents Not Currently Labeled For Intrathecal Usementioning
confidence: 99%
“…It has been reported that equivalent pain control can be achieved with much lower intrathecal doses of hydromorphone than morphine (approximately 20% of morphine doses), with a lower potential for undesirable side effects. 32,33 Medication rotation and a polyanalgesic approach of adding a second or third medication before the concentration or daily dose of any one medication reaches the upper limit of recommendations may prove prudent in reducing the incidence of intrathecal mass propagation. The potential for significant neurologic compromise that may occur with an intrathecal catheter-tip inflammatory mass and the adverse consequences of self-extraction from an intrathecal pump necessitate aggressive assessment and management.…”
Section: Preventionmentioning
confidence: 99%